Problem Solving: A Learning Model to Foster Argumentation and Critical Thinking Ability for Students with Different Academic Abilities - Heffi Alberida; Mutia Sari; Abdul Razak; Syamsuriza Syamsuriza; Yosi Laila Rahmi (Postgraduate, University of Mataram, 2022)
One of the efforts to improve students' argumentation and critical thinking skills in 21st century learning is to apply problem solving learning models by paying attention to students' academic abilities. The type of research used is quasi-experimental with a 2x2 factorial design. The study population was students of class VIII SMPN 18 Padang, while the research sample was students of class VIII.8 and class VIII.7 by taking samples based on certain criteria. The instrument is a data collection technique with a written test. Data analysis was performed by testing the two-way ANOVA hypothesis using SPSS. The results showed that: (1) the problem-solving learning model affected students' argumentative skills and critical thinking. (2) the problem-solving learning model affects the argumentative and critical thinking abilities of students with high and low academic abilities. (3) there is no interaction between the problem-solving learning model and the academic ability of students 'argumentation skills (4) there is an interaction between the problem-solving learning model and the academic ability of students' critical thinking skills. To sum up, problem solving learning model is able to realize students who have critical thinking skills and arguments that can compete in the era of globalization needed in this 21st century education